Open Enrolment and Student Achievement - Jane Friesen; Benjamin Cerf Harris; Simon D. Woodcock (Institute for the Study of Labor (IZA), 2013)
We investigate the effects of public school open enrolment, which allows students to enroll in any public school with available space, on fourth grade test scores. We find a small, positive effect on the average student; this benefit appears to stem from increased competition among schools, rather than directly through expanded choice opportunities. Among students whose catchment school is locally top-ranked according to test scores, greater choice is of no direct benefit; however, students whose catchment school is locally lowest-ranked earn higher scores when they have access to better local schools. Students in both groups benefit from increased school competition.
Keywords: I21; I28; 330; open enrolment; school choice; school competition